FAKTOR-FAKTOR YANG MEMENGARUHI VOLUME EKSPOR TEH HITAM SEBELUM DAN SELAMA MASA PANDEMI COVID-19 (Suatu Kasus Di PT XYZ, Jawa Barat) - Medi Atikah Sari; Lies Sulistyowati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
PT XYZ is a state-owned enterprise in West Java that exports most of its black tea production to the international market. However, the Covid-19 pandemic began to hit Indonesia in early March, which had an impact on economic aspects, one of which was international trade. The purpose of this study is the impact of the value of domestic prices, export prices, the exchange rate of the rupiah against the United States dollar, the amount of production, and the Covid-19 pandemic on the export volume of black tea and to compare the average export volume of black tea at PT XYZ before and during the Covid-19 pandemic. This research is quantitative, with primary data collection obtained through interviews and secondary data obtained through archives, papers, and publications from research-related institutions. Monthly time series data were used in this study for 72 months, from January 2016 to December 2021. The analysis used multiple linear regression and different independent sample t-tests with the help of SPSS 28 software. The results showed that the domestic price, export price, the rupiah exchange rate against the US dollar, the amount of production, and the Covid-19 pandemic simultaneously affected the export volume of black tea at PT XYZ. Partially, the rupiah exchange rate against the US dollar affected the volume of black tea exports at PT XYZ. Meanwhile, domestic prices, export prices, total production, and the Covid-19 pandemic did not partially affect the export volume of black tea at PT XYZ. There are significant differences in the average volume of black tea before and during the Covid-19 pandemic.